Child and adolescent mental health services: longitudinal data sheds light on current policy for psychological interventions in the community. Issue 3 (18th September 2017) - Neufeld, Sharon A.S.; Jones, Peter B.; Goodyer, Ian M.
Abstract : Purpose: The purpose of this paper is to expand upon policy implications of a recent study assessing adolescent mental health service contact and subsequent depression. Design/methodology/approach: Review of related evidence from academic and grey literature. Findings: Studies assessing the role of mental health services in reducing mental disorder during adolescence are sparse, and even prevalence figures for adolescent mental disorders are out-of-date. Adolescent mental health service contact rates are shown to fall concurrent with budgetary decreases. School-based counselling is highlighted as an important source of help that may be at risk of being cut. Increased training of General Practitioners and school counsellors is needed to improve efficiency in specialist Child and Adolescent Mental Health Services (CAMHS). Practical implications: Longitudinal studies of young people's mental health should include mental health service usage and its relationship with subsequent mental health outcomes. Social implications: Funding cuts to CAMHS must be avoided, school-based counselling must be protected, and service referrers should be better trained. Originality/value: This paper highlights the need for increased CAMHS data, sustained funding, and improved training for this vital service.